An efficient procedure for genotyping single nucleotide polymorphisms - Ye, Shu (Oxford University Press, 2001)
Analysis of single nucleotide polymorphisms (SNPs) has been and will be increasingly utilized in various genetic disciplines, particularly in studying genetic determinants of complex diseases. Such studies will be facilitated by rapid, simple, low cost and high throughput methodologies for SNP genotyping. One such method is reported here, named tetra-primer ARMS-PCR, which employs two primer pairs to amplify, respectively, the two different alleles of a SNP in a single PCR reaction. A computer program for designing primers was developed. Tetra-primer ARMS-PCR was combined with microplate array diagonal gel electrophoresis, gaining the advantage of high throughput for gel-based resolution of tetra-primer ARMS-PCR products. The technique was applied to analyse a number of SNPs and the results were completely consistent with those from an independent method, restriction fragment length polymorphism analysis.